Dental age estimation and accuracy assessment by Demirjian, Nolla and Willems methods in Nepalese children for predicting the chronological age (Orthodontic Journal of Nepal, 2021)
Introduction: Dental age estimation has been performed by numerous methods worldwide. This study was done to evaluate and compare the validity and accuracy of dental age estimation by Demirjian, Nolla and Willems methods in Nepalese children.Materials and Method: A comparative cross sectional study was conducted on 280 orthopantomography of Nepalese children aged 5-14 years in Kantipur Dental College from December 2020 to September 2021. Dental age was calculated by three methods and difference with chronological age was examined. Descriptive statistics were presented as mean ± SD and median (range). Differences in paired data of chronological and dental ages were examined using Wilcoxon signed rank test. Spearman’s correlation coefficient was used for comparing chronological and dental ages. Regression analysis was performed to derive equation for predicting chronological age from dental age.Results: An underestimation of dental age was observed with Demirjian (-1.17 years), Nolla (-1.06 years) and Willems (-1.32 years) methods which was statistically significant and also across both genders (p